The Influence of Customer Relationship Management (CRM) and Service Quality on Customer Satisfaction at the Bengkalis Chamber of Commerce and Industry - Jannah, Raudahthul; Rosa, Nageeta Tara (Politeknik Negeri Bengkalis, 2024)
This study aimed to determine the effect of Customer Relationship Management (CRM) and Service Quality on Customer Satisfaction at the Bengkalis Chamber of Commerce and Industry. The data type of this research is quantitative. The sample in this study was 100 respondents, data processing using SPSS 27. using the F test, t test and R Square. Analysis method the analysis method used is multiple regression analysis. The results of this study indicate that: (1) The effect of CRM on customer satisfaction has positive and significant impact on customer satisfaction. (2) the effect of service quality on customer satisfaction positive and significant impact on customer satisfaction, and (3) the effect of Customer Relationship Management (CRM) and Service Quality has positive and significant impact on customer satisfaction. The conclusion is that Customer Relationship Management (CRM) and Service Quality simultaneously have a positive and significant effect on customer satisfaction.